1992
DOI: 10.1111/j.1365-2826.1992.tb00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracellular Calcium Oscillations and Gsα Subunit Expression are Inversely Correlated with Secretory Granule Content in Pituitary Cells

Abstract: Cells of the pituitary tumour cell line GH(4) C(1) were exposed to epidermal growth factor, estradiol and insulin for 5 days, a treatment which resulted in 1) increased prolactin storage in secretory granules, 2) the loss of spontaneous [Ca(2+) ](1) oscillations, and 3) a selective reduction of the protein G(s) α, seen in immunoblots, cholera toxin labelling, and vasoactive intestinal peptide stimulation of adenylyl cyclase. In contrast, the glucocorticoid dexamethasone, which increases the expression of G(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…GH4C1 cells are excitable (Taraskevich and Douglas, 1980), containing voltage-gated calcium channels which undergo both spontaneous and inducible (Ozawa and Kimura, 1979;Taraskevich and Douglas, 1980) action potentials mediated by calcium currents. These cells also display spontaneous fluctuations or spikes (Wagner et al, 1993) in [Ca 2]i, and the occurrence of calcium action potentials has been shown to coincide with the initiation of these [Ca 2]i fluctuations (Chiavaroli et al, 1992). The spontaneous calcium spikes are asymmetric, having rising phases which last -0.5 s, and falling phases with mean duration of 1.7 s (K. Brady, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…GH4C1 cells are excitable (Taraskevich and Douglas, 1980), containing voltage-gated calcium channels which undergo both spontaneous and inducible (Ozawa and Kimura, 1979;Taraskevich and Douglas, 1980) action potentials mediated by calcium currents. These cells also display spontaneous fluctuations or spikes (Wagner et al, 1993) in [Ca 2]i, and the occurrence of calcium action potentials has been shown to coincide with the initiation of these [Ca 2]i fluctuations (Chiavaroli et al, 1992). The spontaneous calcium spikes are asymmetric, having rising phases which last -0.5 s, and falling phases with mean duration of 1.7 s (K. Brady, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%